KONSEP, KARAKTERISTIK DAN RASIONAL SUPERVISI PENGAJARAN DALAM TINJAUAN ANALISIS SWOT - Mujtahid Mujtahid (Fak. Tarbiyah UIN Maliki Malang, 2012)
Teaching supervision is always required to improve the quality of teaching and learning processes in schools or madrasah. Actually, supervision activities is creating a vehicle for supervisors and teachers to exchange ideas, sharing knowledge and sharing experiences. This article critically examines the concept, characters and rational teaching supervision in SWOT analysis review. Supervision aims to teach teachers how to guidance which includes; purposes, materials, techniques, methods, approaches, environment and so on. Based on the SWOT analysis, supervision can create opportunities and power through the; development activities need to be encouraged more intensive and structured, reach the opportunities that exist from government policy programs, following the guidance activities in order to improve their skills. Schools can establish cooperation with related agencies for the development of professional skills of teachers, follow the teachings and training to increase insight and knowledge that are relevant to the task of teaching. Meanwhile, anticipation of the challenges and weaknesses, through; establish cooperation with other agencies to provide the opportunity for teachers to get further guidance, engage the teacher in the whole competence development (intellectual, emotional and spiritual) for human resources through the formal and nonformal, development of school facilities and infrastructure that are refer to the main and supporting principles of effectiveness, development of human resources recruitment system based on the competence and professionalism of the school (merit based system), the development of a reward system and punishment to create a healthy culture and the competition for teachers, and increasing self exemplary which is started from the teachers.